Primary liposarcoma of the thoracic spine: case report - Hamlat, Abderrahmane (Springer-Verlag, 2005)
Liposarcoma is a malignant tumor of soft tissue. The thoracic spine is an unusual location, even for metastasis, and to our knowledge, no case of primary pleomorphic liposarcoma of the vertebral body has been reported until now. A female patient presented with paraplegia. She had a previous medical history of mental depression, and complained of dorsal pain for three months following a road accident. Magnetic Resonance Imaging (MRI) revealed a collapse of T7-T8, and the diagnosis of plasmocytoma was made. She was treated with decompressive laminectomy and posterior instrumentation. Histological examination revealed a pleomorphic liposarcoma. She received a course of radiotherapy. At 13 months follow-up she developed pulmonary metastases and rib involvement. The spine is an unusual location for pleomorphic liposarcoma, even as metastasis. The differential diagnoses of this rare entity are discussed, as well as the criteria for diagnosing primary spinal liposarcoma. Although rare, our case demonstrates that liposarcoma should be considered in the differential diagnosis of spinal tumors.